Prevalensi Efek Prisma Pada Mahasiswa Pengguna Kacamata Koreksi Di FKIK UKRIDA Angkatan 2023 - Kencana, Billy Gadi; Far Far, Inggrid Osya; Silaen, Desi Hartati (Universitas Kristen Krida Wacana, 2025)
Prism effect occurs when light rays decentration from the optical center point. Prism effect without prescription is called unwanted prism. This study aims to determine the prevalence of the prism effect in students who wear corrective glasses. This study used a quantitative descriptive method with a cross-sectional design on 78 respondents. Data collection was carried out from September 2023 to October 2023. In this study, 71.8% (56 people) of respondents were female. As many as 52.6% (41 people) of respondents used spherocylinder lenses. The resultant horizontal and vertical prism effects were highest in the 0.00–1.00∆D category, 70.5% (55 people) and 91% (71 people). The most resultant prism base directions at the Base In & Base Down directions as much as 38.5% (30 people). The horizontal prism effect is still within tolerance of 65.4% (51 people) and the vertical prism effect is still within tolerance of 70.5% (55 people). The prevalence of students experiencing the prism effect reached 93.4%. However, most of it within tolerance limits, horizontal 65.4% and vertical 70.5%. It is recommended for optometrists to prescribe glasses and ensure that the glasses have gone through the correct steps to avoid unwanted prism effects.